Job sharing in the endomembrane system: vacuolar acidification requires the combined activity of V-ATPase and V-PPase - Kriegel, Anne; Andrés González, Zaida; Medzihradszky, Anna; Krüger, Falco; Scholl, Stefan; Delang, Simon; Patir, Meliha Gorkem; Pfeiffer, Anne; Krebs, Melanie; Lohmann, Jan U.; Schumacher, Karin (The plant cell, 2015)
The presence of a large central vacuole is one of the hallmarks of a prototypical plant cell, and the multiple functions of this compartment require massive fluxes of molecules across its limiting membrane, the tonoplast. Transport is assumed to be energized by the membrane potential and the proton gradient established by the combined activity of two proton pumps, the vacuolar H+-pyrophosphatase (V-PPase) and the vacuolar H+-ATPase (V-ATPase). Exactly how labor is divided between these two enzymes has remained elusive. Here, we provide evidence using gain- and loss-of-function approaches that lack of the V-ATPase cannot be compensated for by increased V-PPase activity. Moreover, we show that increased V-ATPase activity during cold acclimation requires the presence of the V-PPase. Most importantly, we demonstrate that a mutant lacking both of these proton pumps is conditionally viable and retains significant vacuolar acidification, pointing to a so far undetected contribution of the trans-Golgi network/early endosome-localized V-ATPase to vacuolar pH.